ANALISI PENGGUNAAN SINONIM PADA LIRIK LAGU “BERTAUT” KARYA NADIN AMIZAH - Angriza Sihite; Beslina A. Siagian (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to explore the use of synonyms in the lyrics of the song "Bertaut" written by Nadin Amizah, and how words with similar meanings are chosen to strengthen meaning and emotional expression. Synonyms are defined as words that have similar meanings, but still differ in nuance, intensity, and context of use. This study applies a qualitative descriptive approach by collecting data through the method of listening and recording synonymous words contained in the lyrics. Analysis is carried out using semantic and cognitive approaches to understand the role of these words in expressing inner experiences, emotional relationships, and poetic messages intended by the songwriter. The findings of this study indicate that the use of synonyms in the lyrics of "Bertaut" is contextual and emotional, not absolute synonyms. Synonymous words not only function as lexical variations, but also as stylistic elements to strengthen emotional nuances, maintain continuity of feelings, and build the depth of the relationship between the narrator and the mother figure, the main focus of the song. The choice of words with similar meanings but different nuances highlights intimacy, warmth, and the power of expression. This research provides insight into how synonyms in song lyrics not only enrich the language but also play a crucial role in the formation of meaning and the enhancement of emotional experiences for listeners.